Mild cell disruption methods for bio-functional proteins recovery from microalgae—Recent developments and future perspectives - Phong, Win Nee; Show, Pau Loke; Ling, Tau Chuan; Juan, Joon Ching; Ng, Eng Poh; Chang, Jo-Shu (Elsevier, 2018)
Bio-functional proteins from microalgae have numerous biological properties with health-promoting effects. However, efficient harnessing of bio-functional proteins from microalgae is still in its infancy. One of the major obstacles that hinder the mass production of bio-functional proteins is the presence of resistant cell wall that diminishes the liberation of cell contents. As the bio-functional proteins are very sensitive to denaturation, selecting a mild disruption method to rupture the cell wall, while preserving their bioactivity and functionality, is of vital importance in downstream processing. To ensure the future development of efficient mild disruption methods for maximum recovery of bio-functional proteins from microalgae, this review provides useful information on various mild disruption approaches, current status, potential technologies that are still under development, as well as their advantages and constraints. In particular, those potential technologies that require further attention in the future (namely, explosive decompression, microfluidization, pulsed arc technology and cationic polymer coated membranes) are also discussed in this review.